Development And Validation Of Communication Skills Assessment Tool For Effective Doctor-Patient Consultations In Lahore, Pakistan - Junaid, Dr. Ayesha (Migration Letters, 2024)
Objective: To develop and validate a tool that assesses the communication skills of doctors, and patients during medical consultations in hospitals. Methods: This study is a part of a larger multiphase project that identified the linguistic barriers (related to habitus, capital and field) in communicative practices of doctors, nurses and patients. The Communication Skills Assessment Tool (CSAT) is developed from the identified barriers. The tool development process includes conducting Delphi rounds, assessing the content validity by CVI and CVR, giving weight to each item, and evaluating each item on a Likert scale. The reliability of the developed tool is assessed by pilot testing. This includes evaluating its face validity, psychometric properties, and internal consistency reliability by Exploratory Factor Analysis (EFA). Results: The computations of Delphi tests (in three rounds) results in retaining 39/94 items under four categories. The S-CVI/Ave with the retained items is 95.9%, while their S-CVI/UA is 97.6%. EFA yields 30 items with variance 71.74%. The reliability measure Cronbach alpha is 86.5% Conclusion: CSAT is a valid and reliable instrument to evaluate communicative practices of doctors with patients in hospitals. However, further validation by Confirmatory Factor Analysis (CFA) is required. Medical schools can use CSAT as an evaluation tool for the continuous quality improvement of healthcare communication and patient safety.